1996
DOI: 10.1053/jhep.1996.v23.pm0008621173
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of antibody to hepatitis C virus envelope 2 glycoprotein in patients with chronic hepatitis C virus infection

Abstract: The significance of circulating antibody to hepatitis C HCV E1 corresponds to the pestiviral gp33/gp25 envevirus (HCV) envelope glycoprotein 2 (E2)/nonstructural lope glycoprotein and the flaviviral envelope protein protein 1 (NS1) glycoprotein was studied in 83 patients (M/E), whereas E2/NS1 corresponds to the pestiviral with chronic HCV infection diagnosed by polymerase gp53/gp55 envelope glycoprotein and the flaviviral chain reaction (PCR). E2/NS1 antibody was quantita-NS1. 1 Based on the greater homology b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
11
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
(5 reference statements)
8
11
1
Order By: Relevance
“…Kato et al [22] analyzed the heterogeneity of GBV-C/HGV by single-strand conformation polymorphism in patients with chronic hepatitis and showed that the major strain of GBV-C/HGV had not changed for 4 years. These results suggest that amino acid substitution in the E2 region is not involved in the mechanism of persistent GBV-C/ HGV infection; these findings are consistent with the fact that GBV-C/HGV viremia ceases after the appearance of the GBV-C/HGV-E2 antibody, whereas active replication of HCV continues in the presence of the HCV-E2 antibody [23].…”
Section: Discussionsupporting
confidence: 78%
“…Kato et al [22] analyzed the heterogeneity of GBV-C/HGV by single-strand conformation polymorphism in patients with chronic hepatitis and showed that the major strain of GBV-C/HGV had not changed for 4 years. These results suggest that amino acid substitution in the E2 region is not involved in the mechanism of persistent GBV-C/ HGV infection; these findings are consistent with the fact that GBV-C/HGV viremia ceases after the appearance of the GBV-C/HGV-E2 antibody, whereas active replication of HCV continues in the presence of the HCV-E2 antibody [23].…”
Section: Discussionsupporting
confidence: 78%
“…One HCV 1a serum sample was nonreactive with HCV 2b E2. Thus, as suggested by previous studies with HCV 1a or 1b E2 protein [Harada et al, 1994;Lesniewski et al, 1995;Rosa et al, 1996;Yuki et al, 1996;Lee et al, 1997], the majority of HCVinfected individuals have an antibody response that reacts with E2 protein of multiple genotypes.…”
Section: Resultsmentioning
confidence: 57%
“…Some individuals have antibodies that are reactive with multiple HVR1 sequences and other individuals have a more limited response [Spengler et al, 1996;Yoshioka et al, 1997;Hattori et al, 1998;Mondelli et al, 1999]. Most individuals also possess an antibody response to conformational epitopes within HCV E2 that can be detected with E2 proteins expressed in mammalian cells [Harada et al, 1994;Lesniewski et al, 1995;Rosa et al, 1996;Yuki et al, 1996;Lee et al, 1997;Nakano et al, 1999]. This response is at least partially composed of broadly reactive antibodies because genotype 1 E2 proteins are generally reactive with HCV sera from individuals infected with various genotypes [Harada et al, 1994;Lesniewski et al, 1995;Rosa et al, 1996;Yuki et al, 1996;Lee et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is predicted that anti-E2/NS1 antibodies may have some protective effect in HCV infection. Contrary to the above reports, there are studies which reveal that HCV infection persists despite the presence of a virus-specific cytotoxic T lymphocyte response and circulating antibodies to various HCV proteins [30,39]. Thus, despite the fact that E2/NS1 is an efficient immunogen, the neutralizing capacity of these antibodies remains to be documented and induction of E2-specific cellular immune responses need to be studied extensively.…”
Section: Introductionmentioning
confidence: 86%